Community Service Assistance in the Use of the "BUMDES PECATU" Application to Customers in the Waste Management Unit in Pecatu Village - I Kadek Budi Sandika; Komang Kurniawan Widiartha; Made Suci Ariantini; Wayan Gede Suka Parwita; Desak Made Dwi Utami Putra; I Komang Arya Ganda Wiguna; I Gede Iwan Sudipa (Abdimas Paspama, 2023)
BUMDes Catu Kwero Sedana Pecatu, Pecatu Village utilizes the " BUMDES PECATU" application as an innovative solution in increasing community involvement and optimizing waste management units. Through community service activities that focus on assisting the use of the application, with a door to door approach to customer addresses, the service team supported by the Pecatu village government provides counseling, education, and direct technical support to the community. The results show an increase in understanding and community participation in waste management through the use of the "BUMDES PECATU" application. Regular mentoring activities are expected to ensure the continuity and optimization of the BUMDES PECATU application in supporting operations in the waste management unit and active participation of the village community.